LITERASI MEMBACA ANAK-ANAK DI PESISIR PANTAI SAWARNA, LEBAK BANTEN - Suraya, Suraya; Zubair, Agustina; Wardhani, Diah (Jurnal Pengabdian dan Kewirausahaan, 2019)
This community empowerment activity is in the form of training on the socialization of Reading Literacy to Students in Sawarna Beach, Lebak banten. The purpose of this training the students and school-aged children have the ability to read and become accustomed to reading. This training activity was held on February 13, 2018 in Sawarna Village, Lebak Banten. This activity is followed by students who are domiciled in the village. The participants have not fully read the habit either at home or at school. The lack of facilities for children's story books owned by schools and at home. Children or Students Kindergarten requires motivation and inspiration about activities and reading habits or reading literacy. Keywords : Reading Literacy, Kids, Empowerment Activity